The Spatial Analysis of JNE Agent Distibution in Cibinong District - Andriyana Lailissaum; Muhammad Dimyati (Tunas Geografi, 2022)
The development of buying and selling online is increasing every year. This also resulted in an increase in the number of package deliveries to freight forwarders, including JNE. Therefore, establishing a JNE agent is a potential business. The requirement to establish a JNE agent is that the location must be at least 1 Km from the location of other JNE agents. The purpose of this study was to find alternative locations for the establishment of JNE agents. This study uses spatial analysis to analyze the distribution of JNE agents in Cibinong District. Some of the spatial analyzes used include Nearest Neighbour Analysis (NNA), Normalized Difference Built-Up Index (NDBI), Buffer and weighted overlay. The results obtained indicate that the distribution of JNE agents in Cibinong District tends to spread. Some JNE agents are less than 1 Km from other JNE agents. Most of the JNE are located on roads with the status of local roads and a radius of about 500 meters around JNE on average there are about 52% of the built area. According to this study, there are only a few suitable locations to establish a JNE agent in Cibinong District.